2018
DOI: 10.3892/ijmm.2018.3778
|View full text |Cite
|
Sign up to set email alerts
|

Long non‑coding RNA urothelial cancer associated�1 regulates radioresistance via the hexokinase�2/glycolytic pathway in cervical cancer

Abstract: Cervical cancer is one of the most common types of female malignant tumor. It is well established that radiotherapy (RT) is the first‑line treatment of cervical cancer; however, radioresistance is a substantial obstacle to cervical cancer RT. At present, the mechanism underlying radioresistance remains unclear. Emerging evidence has demonstrated that long non‑coding RNAs (lncRNAs) function as crucial regulators of diverse cancers. Aerobic glycolysis, which is a common phenomenon in cancer cells, is associated … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
49
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 50 publications
(50 citation statements)
references
References 31 publications
1
49
0
Order By: Relevance
“…Interestingly, mitochondrial TIGAR-HK2 complex upregulated HK2 and hypoxia-inducible factor 1 activity limiting reactive oxygen species production and protecting from tumor cell death under hypoxic condition implying that p53 could be an essential key regulator for HK2-mediated oncogenesis (26,30,48). In addition to signaling factors, HK2 regulated by epigenetic mediators including microRNAs (32,(52)(53)(54)(55), long non-coding RNAs (56)(57)(58), and histone/DNA methylation (59) are also important to modulate HK2-mediated tumorigenicity. Taken together, HK2 seems to be a master promoting factor in controlling carcinogenesis in different cancers; to date, however, the role of HK2 in controlling head and neck squamous cell carcinoma (HNSCC) development was rarely focused.…”
Section: Introductionmentioning
confidence: 99%
“…Interestingly, mitochondrial TIGAR-HK2 complex upregulated HK2 and hypoxia-inducible factor 1 activity limiting reactive oxygen species production and protecting from tumor cell death under hypoxic condition implying that p53 could be an essential key regulator for HK2-mediated oncogenesis (26,30,48). In addition to signaling factors, HK2 regulated by epigenetic mediators including microRNAs (32,(52)(53)(54)(55), long non-coding RNAs (56)(57)(58), and histone/DNA methylation (59) are also important to modulate HK2-mediated tumorigenicity. Taken together, HK2 seems to be a master promoting factor in controlling carcinogenesis in different cancers; to date, however, the role of HK2 in controlling head and neck squamous cell carcinoma (HNSCC) development was rarely focused.…”
Section: Introductionmentioning
confidence: 99%
“…1 shows four lncRNAs related to glycolysis: (1) lncRNA Ftx promotes the expression of peroxisome proliferator-activated receptor γ (PPARγ), and PPARγ upregulates the expression of enzymes in carbohydrate metabolism, which ultimately enhances aerobic glycolysis in HCC. In addition, the alterations in lactate production, glucose uptake and the enzyme expression induced by Ftx can be counteracted by downregulating the expression of PPARγ [28]; (2) lncRNA UCA1 promotes glycolysis by upregulating hexokinase 2 (HK2) in cervical cancer [29]; (3) lncRNA-p23154 suppresses the expression of miR-378a-3p, and miR-378a-3p can promote Glut1-mediated glycolysis in oral squamous cell cancer by binding and inhibiting Glut1 [30]; and (4) lncRNA CRYBG3 increases the expression of lactate dehydrogenase A (LDHA), and LDHA promotes glycolysis in lung cancer. Furthermore, glycolysis can enhance cell proliferation [31].…”
Section: Promoting Glycometabolismmentioning
confidence: 99%
“…Long non-coding RNAs (lncRNAs) are a family of non-coding RNAs (ncRNAs) that have less than 200 bases in length and possess limited ability for protein-coding (11)(12)(13)(14). Numerous studies have confirmed that dysregulation of lncRNA expression is associated with the development of a number of tumors (15)(16)(17). It is well established that lncRNAs play important roles in the regulation of a battery of cellular and biological processes, including development, differentiation, de-differentiation, proliferation, autophagy and apoptosis (18).…”
Section: Introductionmentioning
confidence: 99%